Bioactive compounds of red wine production waste: health effects and benefits - Sevi Gedikoglu; Haya Alghalibi; Cevdet Efe Ozdas; Gizem Bilek; Khatuna Diasamidze (Georgian Medical Journal, 2026)
Cardiovascular disease remains the leading cause of global mortality, and there is continued interest in dietary compounds that reduce oxidative stress, chronic inflammation, endothelial dysfunction, and atherosclerotic progression. Red wine has been associated with a lower risk of cardiovascular disease — a phenomenon known as the "French paradox" — and most of its proposed benefits are attributed to polyphenolic constituents rather than ethanol. During vinification, large amounts of grape pomace, seeds, and skins are produced, and these winery by-products contain high concentrations of the same bioactive compounds found in wine. This narrative review summarises the evidence regarding the cardiovascular benefits of red wine polyphenols and wine production waste. Key bioactive constituents include quercetin, catechins, anthocyanins, flavonoids, resveratrol, and phenolic acids, which exhibit antioxidant, anti-inflammatory, anti-platelet, and vasoprotective actions. At the molecular level, they inhibit low-density lipoprotein oxidation, suppress NF-κB signalling and pro-inflammatory cytokine production, enhance endothelial nitric oxide synthase activity, and improve nitric oxide bioavailability. Evidence also indicates that red wine polyphenols influence gut microbiota composition and confer vascular protection via epigenetic and mitochondrial signalling pathways, extending their influence beyond direct radical scavenging. Despite promising preclinical and observational findings, translation into clinical practice remains limited by inconsistent dosing strategies, variable bioavailability, and confounding effects of ethanol exposure. Future research should focus on standardised clinical trials of dealcoholised wine and purified polyphenol extracts from grape by-products to identify safe, evidence-based cardiovascular interventions. Keywords: red wine; polyphenols; cardiovascular disease; resveratrol; grape pomace; French paradox; endothelial function; wine by-products; antioxidant; flavonoids